The handbook of juvenile delinquency and juvenile justice - Krohn, Marvin D.; Lane, Jodi, 1967- (Chichester, West Sussex, UK ; Malden, MA : John Wiley & Sons, 2015)
This handbook is an up-to-date examination of advances in the fields of juvenile delinquency and juvenile justice that includes interdisciplinary perspectives from leading scholars and practitioners. Examines advances in the fields of juvenile delinquency and juvenile justice with interdisciplinary perspectives from leading scholars and practitioners Provides a current state of both fields, while also assessing where they have been and defining where they should go in years to come Addresses developments in theory, research, and policy, as well as cultural changes and legal shifts Contains.
Juvenile Dispositions and Corrections -- Punishment and/or TreatmentConclusion; Notes; References; Part II Correlates of Delinquent Behavior; Chapter 9 Gender, Delinquency, and Youth Justice: Issues for a Global Century; Boys' Crime and Gender: A Neglected Topic; Criminalizing Victimization: Girls' Lives and the Criminal System; Conclusion; Notes; References; Chapter 10 Causes of African-American Juvenile Delinquency; Where Have We Been?; Where Are We Now?; A Race-Centered Analysis of African-American Juvenile Delinquency; Where Do We Go From Here?; References.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Juvenile delinquency; Juvenile justice, Administration of; Juvenile delinquency; Juvenile justice, Administration of; Juvenile justice; Juvenile delinquency; Juvenile justice, Administration of; Electronic books; Electronic books